2011
DOI: 10.1111/j.1467-9221.2010.00820.x
|View full text |Cite
|
Sign up to set email alerts
|

God and Country: The Partisan Psychology of the Presidency, Religion, and Nation

Abstract: Overt love of God and country have seemingly been prerequisites to be president in the United States in recent decades, if not always. Indeed, the 2008 presidential race was replete with campaign messages showcasing such perspectives-that Barack Obama and John McCain were religiously faithful and deeply patriotic. Scholarship demonstrates the potential political power of explicit appeals to America and Christianity; however, little research has examined (a) citizens' perceptions of candidates' ties to faith an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 56 publications
1
30
0
Order By: Relevance
“…Sheets, Domke, and Greenwald (2011) demonstrated that the IAT provided more predictive validity than self-reports of attitudes and voting intentions for the 2008 U.S. presidential election. The IAT contained images of John McCain and Barack Obama as well as images and words regarded as symbolic of patriotism and Christianity in contrast to non-American and non-religious stimuli.…”
Section: Implicit Measures and Votingmentioning
confidence: 98%
“…Sheets, Domke, and Greenwald (2011) demonstrated that the IAT provided more predictive validity than self-reports of attitudes and voting intentions for the 2008 U.S. presidential election. The IAT contained images of John McCain and Barack Obama as well as images and words regarded as symbolic of patriotism and Christianity in contrast to non-American and non-religious stimuli.…”
Section: Implicit Measures and Votingmentioning
confidence: 98%
“…(Sheets, Domke, and Greenwald 2011). ix The FreeIAT software can downloaded from <http://www4.ncsu.edu/~awmeade/FreeIAT/FreeIAT.htm>.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the BIAT has found application in many studies already [10][11][12][13] The present studies analyzed data from a very large data collection in a study that administrated a random selection of measures of attitudes regarding race, politics and the self from a large pool of possible indirect and direct attitude measures [14], comparing the psychometric qualities of seven different indirect measures on a wide variety of criteria. The BIAT was the best of the seven measures in 8 out of the 29 criteria used to evaluate the measures as measures of attitudinal preference, and the second best in another 8 criteria (always outperformed only by the IAT).…”
Section: The Brief Implicit Association Testmentioning
confidence: 99%